Reducing Administrative Barriers Increases Take-Up of Subsidized Health Insurance Coverage: Evidence from a Field Experiment - Ericson, Keith Marzilli; Layton, Timothy J.; McIntyre, Adrianna; Sacarny, Adam (The Review of Economics and Statistics, 2025)
Administrative barriers to social insurance program take-up are pervasive, including in subsidized health insurance. We conducted a randomized controlled trial with Massachusetts' Affordable Care Act marketplace to reduce these barriers and other behavioral frictions. We find that a “check the box” streamlined enrollment intervention raises enrollment by 10.5%, more than personalized reminder letters (7.6% increase) or generic reminder letters (4.3% increase). Effects are concentrated among individuals eligible for zero-premium plans, who faced no further administrative burdens of setting up payments. Producing this enrollment effect through premium reduction would cost about $7 million in subsidies, highlighting the importance of these burdens.